A Pilot Study Examining Speed of Processing Training (SPT) to Improve Processing Speed in Persons With Multiple Sclerosis - Chiaravalloti, Nancy D.; Goverover, Yael; Costa, Silvana L.; DeLuca, John (Frontiers in Neurology, 2018)
Background: Individuals with Multiple Sclerosis (MS) have significant impairments in processing speed (PS) and such impairments may underlie other cognitive deficits common in MS and limit performance of everyday life activities. Objective: To examine the efficacy of a computerized PS intervention, Speed of Processing Training (SPT), in persons with MS on PS, memory and everyday activities. Methods: Twenty-one individuals with clinically definite MS and an objectively assessed impairment in PS were included in a controlled randomized clinical trial, randomly assigned to a treatment group or a control group. Participants were assessed prior to and within 1 week of completing the treatment. Outcome measures included traditional neuropsychological tests measuring PS and memory, and an assessment of PS in daily life activities. Results: The treatment group showed a significant improvement on neuropsychological tests of PS and new learning and memory. A significant improvement was additionally noted in the treatment group on measures of PS in everyday life. These changes were not observed in the control group. Conclusions: Results provide preliminary data in support of SPT in treating PS deficits in persons with MS. Additional research is needed with larger samples and more comprehensive outcome measures.